Theory and Data in a Computational Model of Secularization - Shults, Fount LeRon (Bulletin for the study of religion, 2021)
This article illustrates the value of computer modeling and simulation (CMS) for linking theory and data in the academic study of religion, focusing on ways in which scholars in religious studies and the humanities can benefit by collaboratively engaging in this relatively new and radically transdisciplinary methodology. I begin by briefly introducing CMS and describing some of its recent uses in analyses of religious phenomena. The second part provides a case study - an agent-based model (ABM) designed to simulate and forecast changes in religiosity and existential security in Europe (Gore et al. 2018). The main research question guiding the construction and validation of this model was: What are some of the conditions under which - and mechanisms by which - religiosity declines in contemporary European populations? I highlight one of the main research findings from the simulation experiments on the model. Finally, I briefly explore some of the material and methodological implications of the development and deployment of such models for the academic study of religion.